Serine 162, an essential residue for the mitochondrial localization, stability and anti-apoptotic function of Mcl-1. - Luke W Thomas; Connie Lam; Richard E Clark; Michael R H White; David G Spiller; Robert J Moots; Steven W Edwards (PLoS ONE)
Mcl-1 is an anti-apoptotic member of the Bcl-2 family that plays a key role in normal development, but also in pathologies such as cancer. It has some unusual properties compared to other anti-apoptotic members of the Bcl-2 family, and its expression and function are dynamically regulated by a variety of post-transcriptional and post-translational processes. Of note, Mcl-1 protein has a very short half life, and its stability and function may be regulated by reversible phosphorylation. There is also evidence to suggest that it may be localized to different subcellular compartments. The aim of this work was to determine whether residues within the PEST region of Mcl-1 that may undergo reversible phosphorylation, also regulate its subcellular distribution. We show that EGFP:Mcl-1 localizes mainly to the mitochondria of HeLa cells, with some additional cytoplasmic and nuclear localization. The mutations, S64A, S64E, S121A, S159A, T163A and T163E did not significantly affect the localization of Mcl-1. However, mutation of Ser162 to the phospho-null residue, Alanine resulted in an essentially nuclear localization, with some cytoplasmic but no mitochondrial localization. This mutant Mcl-1 protein, S162A, showed significantly decreased stability and it decreased the ability to protect against Bak-induced apoptosis. These data identify a new molecular determinant of Mcl-1 function, localization and stability that may be important for understanding the role of this protein in disease.